Pengaruh Disiplin Kerja, Kompensasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada Pegawai Cv. Istana Mobil - Arifin, Indra Welly; Febrianto, Vidi; Tarigan, Hendri Mayanta (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
This study aims to determine the effect of work discipline, compensation and job satisfaction on nurse performance in employees of CV. Car Palace. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to employees of CV. Istana Mobil as many as 98 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicolonearity test, heteroscedasticity test, multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing, namely the T test. The results of SPSS in this study are the work discipline variable (X1) has an effect on the performance variable (Y). ), the compensation variable (X2) has no effect on the performance variable (Y), the job satisfaction variable (X3) has no effect on the performance (Y), and the hypothesis test is the F test of work discipline (X1), compensation (X2), and job satisfaction (X3) has a simultaneous effect on performance (Y)